2021
DOI: 10.3390/diagnostics11122262
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling Variations in Celiac Trunk and Hepatic Artery by CT Angiography to Aid in Surgeries of Upper Abdominal Region

Abstract: Understanding of variations in the course and source of abdominal arteries is crucial for any surgical intervention in the peritoneal space. Intricate surgeries of the upper abdominal region, such as hepato-biliary, pancreatic, gastric and splenic surgeries, require precise knowledge of regular anatomy and different variations related to celiac trunk and hepatic artery. In addition, information about the origin of inferior phrenic artery is important in conditions such as hepatocellular carcinoma and gastroeso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 59 publications
1
7
0
Order By: Relevance
“…Celiac mesenteric trunk (typeVI) was also observed in north Indian population with the frequency of 0.91% individual. This type of variation was also found in our study participants in Urdu speaking individual with the frequency of 0.625% individual (26) . Though in our study Type IV and type VI was only found in Urdu speaking individuals.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Celiac mesenteric trunk (typeVI) was also observed in north Indian population with the frequency of 0.91% individual. This type of variation was also found in our study participants in Urdu speaking individual with the frequency of 0.625% individual (26) . Though in our study Type IV and type VI was only found in Urdu speaking individuals.…”
Section: Discussionsupporting
confidence: 87%
“…Frequency of hepatogastric trunk in Turkish population was reported to be 1% (16) while in Brazalians it was reported to be 1.7% i.e 1 individual each (30) . A study conducted on north Indian population published in 2021 showed Hepatogastric trunk with the frequency of 1.82% cases (26) while in south Indian population hepatogastric trunk was not present (27). Present study showed hepatogastric trunk was only present in Pathan speaking.…”
Section: Discussionmentioning
confidence: 46%
See 2 more Smart Citations
“…However, this procedure is technically challenging and requires expertise in ultrasound imaging, visceral arterial hemodynamics, and duplex scan interpretation. On the other hand, CTA with 2D and 3D imaging can provide excellent reconstructions of the visceral arteries and is recommended as the initial imaging study in many studies [4,[27][28][29][30][31][32][33][34][35][36][37]. Furthermore, centerline analysis may be helpful in increasing the accuracy of the measurement of the stenosis and is especially appropriate for preoperative planning of endovascular treatment.…”
Section: Discussionmentioning
confidence: 99%